The role of built environment in fostering the safety of children with autism in public primary schools - Hamed, Riham (My University, 2023)
Background: A wide body of evidence shows that children with autism spectrum disorders encounter many struggles in public education system especially in the developing countries like Egypt, including exposure to problem behavior and limited resources. It can consequently be hypothesized that the school design and space planning can have a considerable impact on enhancing the physical and psychological safety of ASD students through logical school zoning, bullying suppression, and facilitated wayfinding. Methods: This study utilized a mixed method approach to further understand how school design can foster the safety of ASD children. First, the spatial layout of two primary public schools, in Egypt and the United States were analyzed and compared to examine: (1) the schools’ zoning and space planning, (2) the natural surveillance provided by the schools’ buildings’ design through space syntax analysis using DepthmapX software, and (3) the space organization of the schools and how that affects the wayfinding. Second, a survey (n=312) was conducted to understand the perspectives of teachers, in Egypt and the US, regarding the safety of children with autism in public schools. Results: The study findings showed that multiple design elements in the Egyptian school would result in suppressing the natural surveillance and wayfinding of children with autism like (1) concealed nooks, (2) corridors with limited widths, (3) multiple exits, (4) low-transparency classroom windows, and (5) dispersed classrooms zones and restrooms’ locations. Unlike the examined school in the US, the design helped foster natural surveillance and facilitated wayfinding in many ways which consequently would foster the safety of ASD students. Further, the teachers discussed multiple themes when asked to identify affect the safety of ASD children either positively or negatively. Among the identified themes: (1) Bullying, (2) Elopement, (3) Un-monitored Exits, (4) Sensory rooms, (5) Safe places, (6) Wayfinding, and (7) Un-educated teachers. Unexpected findings were also identified to affect the safety of ASD children in public schools according to the teachers’ responses including, (1) routine, (2) types of bullying, (3) Walking distance, (4) Exclusion, (5) communication boards, and (6) shortage of staff. In conclusion, major findings in literature and identified through the study analysis were utilized to suggest implications for practitioners toward designing safer schools for children with ASD.
Keywords: School Design; Space Syntax; Autism Spectrrum Disorders; Safety; Bullying; Natural Surveillance; Space planning; Inclusive Education; Public Schools; Wayfinding; Visibility; Architecture